The Influence of Transformational Leadership Style, Work Environment and Organizational Culture on Employee Job Satisfaction at PT Bhinneka Tekno Sejati - Guslina, Indri (Green Publisher Indonesia, 2025)
This study aims to determine how much influence Leadership Style, Organizational Culture and work environment have on employee job satisfaction at PT Bhinneka Tekno Sejati. This study was conducted at PT Bhinneka Tekno Sejati. This study uses a quantitative approach. The sampling technique, namely the saturated sample method in this study, is a technique for determining samples from the population that is carried out for the entire population without considering strata in the population. The data collection technique uses observation in the form of a questionnaire. The data processing techniques used in this study are validity testing, reliability testing, multiple linear regression testing, determination coefficients, and simultaneous tests. The variables of the transformational Leadership style (X1), work environment (X2), Organizational Behavior (X3), job satisfaction (Y), the results of the validity test have a CITC value greater than 0.30. The results of the study obtained a significant level of P-value (0.000) <0.05, which means that there is an influence between Transformational Leadership Style on Job Satisfaction, which is 72,3%. There is an influence between Work Environment on Job Satisfaction, which is 75,5%. There is an influence too between Organizational Behavior on Job Satisfaction which is 86,5%. And there are influence between Transformational Leadership Style, Work Environment and Organizational Behavior on Job Satisfaction which are 88%.